The Ideology And Doctrine of Muhammadiyah - Tasminatin Tasminatin; Moh. Nurhakim; Zulkarnaini Zulkarnaini (Green Publisher Indonesia, 2026)
This research discusses the ideology and doctrine of *The Ideology And Doctrine Of Muhammadiyah*, which is reflected in the Muqaddimah of the Muhammadiyah Articles of Association (MADM), the Principles of Muhammadiyah Beliefs and Ideals (MKCH), and the Personality of Muhammadiyah as the foundation of the da'wah and reform movement. This study is important for understanding the identity, direction of struggle, and contribution of Muhammadiyah to the life of the people and the nation. The purpose of this research is to analyze the concept of Muhammadiyah ideology and its relevance in facing contemporary developments. This study employed a qualitative approach with a descriptive-analytical method. Data were obtained through a literature review of Muhammadiyah’s official documents, such as the Articles of Association, MKCH, as well as scholarly works related to Muhammadiyah’s thoughts and movement. Data analysis was conducted using content analysis techniques to examine the ideological values contained in the documents. The results of the study show that the Muqaddimah of the Muhammadiyah Articles of Association affirms monotheism as the theological foundation of the struggle, MKCH emphasizes the orientation of da'wah amar ma'ruf nahi munkar and tajdid, while the Personality of Muhammadiyah serves as a moral and ideological guideline for all members of the organization. These values form the identity of Muhammadiyah as a progressive, rational Islamic movement oriented toward the benefit of the people. Thus, Muhammadiyah ideology remains relevant in responding to social, scientific, and national challenges in the modern era.